Nonsurgical Treatment of Type II Dens Invaginatus in a Maxillary Lateral Incisor Using Cone-Beam Computed Tomography - Afkar, Mohsen; Gholamshahi, Masoomeh; Mohammadi, Mehdi (Iranian Endodontic Journal, 2019)
This is a clinical report of a case of Oehlers type II dens invagination in left maxillary lateral incisor. A 12-year-old female patient was referred to endodontic department of Islamic Azad University. She reported history of pain and swelling on left anterior maxilla. Due to the insufficient information from conventional radiography, cone-beam computed tomography (CBCT) was ordered. CBCT revealed apical lucency and two separate canals. Conventional root canal therapy was done using warm vertical technique for invaginated canal. One year follow-up radiographies showed periapical repair and absence of symptoms. Key Words: Cone-Beam Computed Tomography; Dens Invaginatus; Maxillary Lateral Incisor